The effects of covid-19 on rural school communities in Guyana: New directions or old methods retooled - Bissessar, Charmaine (My University, 2022)
The true effect of the pandemic will not be felt for many years. However, the present effect of the pandemic has resulted in a digital canyon between the haves and have nots concerning accessibility to devices and Internet connectivity. Rural school communities are feeling the effects of the pandemic. This qualitative methodology, based on the descriptive phenomenology approach, examined the views of a purposive sampling of 12 secondary school teachers who are teaching in rural Guyana (hinterland) regions, in order to understand some of the issues they and their students are facing. The issues were learning loss, the COVID slide, and digital divide. In order to mitigate these effects the teachers have been using first- and second-generation media (community boards, radio, and supermarket distribution sites). Their resilience and grit are evidenced as they continue the education process. Rural communities have galvanized into action to provide spaces for sharing worksheets and to ensure that no child is left behind.
Keywords: Covid-19; rural schools